Preparation method and application of composite porous carbon-based negative electrode material with hard carbon coated with soft carbon
By using multi-layer coating technology of dopamine polyethylene glycol-based silane and phenolic resin in hard carbon coated soft carbon composite porous carbon, the problem of insufficient adhesion of core-shell structure is solved, and the circulation performance of the material is significantly improved and Compressive resistance, suitable for lithium battery negative electrode materials.
Patent Information
- Application Number
- CN202411773589.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing hard carbon coated soft carbon composite porous carbon core structure lacks adhesion, resulting in structural instability, affecting cycling and compressive resistance.
The soft carbon core is surface grafted and modified by dopamine polyethylene glycol silane, and copolymerized with dopamine monomer in situ to form an organic silicon-polydopamine coating layer, and then polymerized in situ on its surface to form a phenolic resin, forming three The hard carbon of the layer structure coats the soft carbon composite porous carbon.
It has achieved the stability improvement of the core-shell structure, enhanced the circulation and compressive resistance of the material, and is suitable for the negative electrode material of lithium batteries.
Smart Images

Figure CN119252907B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary battery negative electrode materials, and in particular relates to a preparation method and application of a composite porous carbon-based negative electrode material of hard carbon coated with soft carbon. Background Art
[0002] With the continuous increase in the demand for energy and power due to the development of science and technology, as well as the demand for long-lasting and ultra-fast charging batteries, the traditional lithium battery negative electrode material graphite has been developed to a level close to the theoretical capacity. The theoretical specific capacity of silicon materials can reach 4200mAh / g, which is more than 10 times that of traditional graphite negative electrode materials. However, the main reason why silicon-based negative electrode materials are not widely used is that silicon will expand 3 times its original volume during the lithiation process, which is fatal to lithium batteries. Silicon-carbon composite materials are currently an effective means to solve the low specific capacity and alleviate the silicon expansion effect. For example, chemical vapor deposition silicon-carbon negative electrode materials are prepared by cracking silane gas in porous carbon channels to generate nano-silicon. The performance of the porous carbon substrate used has a great influence on the final product. Porous carbon substrate materials include hard carbon and soft carbon, each with its own advantages and disadvantages. Hard carbon is mainly composed of biomass, high molecular organic matter and resin. Due to the inherent large pores of biomass hard carbon materials, it is difficult to regulate the pore structure through activation, and the raw materials are greatly affected by the natural environment and are difficult to stabilize; resin hard carbon materials can obtain a porous structure with controllable pore structure through activation reaction, and the raw materials are stable, the impurity content is low, and the structural strength is high, but the price is high, and it is difficult to apply it on a large scale in the power battery market. In addition, the short-range disordered structure of hard carbon leads to a relatively fast diffusion rate of lithium ions and good compatibility with electrolytes, so it has a higher rate performance, but too many holes will also lead to a larger specific surface area and low initial charge and discharge efficiency. Soft carbon has a wide range of raw materials, low price, good conductivity and a faster lithium ion transmission rate, but due to its poor strength and high expansion rate, it cannot effectively withstand the volume expansion of silicon, nor is it enough to prevent the agglomeration of silicon particles.
[0003] Utilizing the respective advantages of hard carbon and soft carbon, preparing composite carbon by combining hard carbon and soft carbon is an important research direction for silicon-carbon negative electrode materials. Chinese patent CN113889593B discloses a method for preparing a hard carbon-coated soft carbon composite material, which comprises the following steps: 1) subjecting a precursor liquid containing an asphalt compound, titanium dioxide, and an organic solvent to a hydrothermal reaction to obtain a core precursor particle; 2) dissolving a hard carbon precursor, a lithium salt, and benzenesulfonic acid in a solvent to obtain a coating solution, coating the core precursor particles with the coating solution, and then carbonizing; the hard carbon precursor is one or more of phenolic resin, epoxy resin, polyfurfuryl alcohol, furfural resin, furfural ketone resin, and furfuryl alcohol resin. The hard carbon-coated soft carbon composite material obtained by this method has TiO2-doped soft carbon as the core, which can improve the specific capacity and lithium ion transmission capacity, improve the structural stability of the material and the safety of battery operation; the hard carbon in the outer shell has the characteristics of large interlayer spacing and stable structure, which is beneficial to improving the fast charging performance and cycle performance of the material, and the lithium salt is used to supplement the hard carbon material with lithium to improve the material's initial efficiency and rate performance.
[0004] Chinese patent CN111293301B discloses a soft and hard carbon composite porous negative electrode material for sodium ion batteries and a preparation method thereof. The soft and hard carbon composite porous negative electrode material is prepared by regulating cobalt nitrate, dimethyl imidazole and polyvinyl alcohol. The preparation method is: adding an ethanol solution of dimethyl imidazole dropwise to an ethanol solution of cobalt nitrate, stirring at room temperature to form a solution of the precursor ZIF-67; then adding polyvinyl alcohol to the solution, then refluxing to form a gel, cooling it naturally, freeze-drying it, and then placing it in an inert gas atmosphere at 700-1100°C for 2-5 hours to obtain the negative electrode material. The present invention is to synthesize a soft carbon carbon source metal organic framework ZIF-67 first, then add a hard carbon carbon source PVA to form a gel, and obtain the final product after heat treatment. The composite negative electrode material prepared by the present invention combines the advantages of the excellent conductivity of soft carbon and the high capacity of hard carbon, effectively improves the stability of the battery, and improves the cycle performance and coulomb efficiency of the sodium ion battery. The raw material composition used in the method is stable, the process operation is simple, the repeatability is high, and it is conducive to industrial production.
[0005] The composite porous carbon of hard carbon coated with soft carbon prepared in the above patents are all physically coated, and there is insufficient bonding between the core and the shell, and the outer shell is easily peeled off, that is, the structure is not stable enough, which will adversely affect the cycle performance and compressive resistance. Summary of the invention
[0006] In view of the fact that the composite porous carbon prepared by the above-mentioned hard carbon coated soft carbon still has the problem of insufficient bonding force between the core and shell, that is, structural instability, the present invention provides a method for preparing a composite porous carbon-based negative electrode material of hard carbon coated soft carbon. The core-shell structure of the composite porous carbon prepared by this method is stable and contains doped elements. The negative electrode obtained after chemical vapor deposition of silicon and activation has good electrochemical properties, especially excellent cycle performance and compressive resistance.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a composite porous carbon-based negative electrode material of hard carbon coated with soft carbon, comprising the following steps:
[0009] (S1) carbonizing, activating and crushing a soft carbon material precursor to obtain soft carbon core particles;
[0010] (S2) soaking the soft carbon core particles in an oxidizing inorganic strong acid, rinsing and drying after soaking to obtain oxidized soft carbon; then dispersing the oxidized soft carbon in a mixed solution of dopamine polyethylene glycol silane and an aromatic solvent for grafting reaction to obtain modified soft carbon; then adding the modified soft carbon and dopamine to a Tris-HCl buffer solution for in-situ copolymerization reaction, and after the reaction is completed, centrifuging, washing, and drying to obtain composite particles of organosilicon-polydopamine coated soft carbon; the structural formula of the dopamine polyethylene glycol silane is:
[0011] ;
[0012] Wherein, R is methyl or ethyl, and n is an integer of 5 to 15;
[0013] (S3) adding the composite particles of organosilicon-polydopamine coated soft carbon and a surfactant into an alcohol aqueous solution to form a suspension, then adding a phenolic monomer, polyformaldehyde and an alkali catalyst to the suspension, heating the suspension to perform an in-situ polymerization reaction; after the reaction is completed, centrifuging, drying and solidifying the suspension to obtain composite particles of phenolic coated soft carbon;
[0014] (S4) The composite particles of phenolic coated soft carbon are carbonized and activated to obtain composite porous carbon of hard carbon coated soft carbon;
[0015] (S5) Chemical vapor deposition is performed on the composite porous carbon using an organic silicon source gas, so that part or all of the nano-silicon particles are attached to the pores of the porous carbon; then, a gas-phase carbon source is used to perform vapor deposition to form a carbon coating layer, thereby obtaining a composite porous carbon-based negative electrode material in which hard carbon is coated with soft carbon.
[0016] After oxidation, the soft carbon core particles generate abundant oxygen-containing functional groups such as -OH and -COOH on the surface, which is beneficial to the subsequent grafting modification. During the grafting modification of dopamine polyethylene glycol silane, the oxygen-containing functional groups such as -OH and -COOH on the surface of the soft carbon core particles react with the silane alkoxy groups, thereby introducing dopamine polyethylene glycol silane to the surface of the soft carbon core particles by chemical bonds; then the active dopamine groups on the surface of the grafted modified soft carbon are copolymerized with the dopamine monomer, so that polydopamine is in situ coated on the surface of the soft carbon to form composite particles of organosilicon-polydopamine coated soft carbon; then, phenolic resin is in situ polymerized on the surface of the composite particles of organosilicon-polydopamine coated soft carbon, that is, a three-layer structure is formed, with the inner layer being soft carbon, the middle layer being organosilicon-polydopamine, and the outer layer being phenolic. Since it is an in-situ copolymerization, and the dopamine polyethylene glycol silane of a certain chain length can form an effective complement with the short-chain dopamine monomer, the organosilicon-polydopamine in the middle layer can densely, evenly and stably cover the soft carbon; at the same time, since the polydopamine in the middle layer has strong adhesion properties, and the abundant hydroxyl groups and amino groups in the polydopamine can form strong hydrogen bonding forces with the phenolic aldehyde in the outer layer, thereby enhancing the bonding force between the two, so that the phenolic aldehyde in the outer layer is firmly and stably coated on the middle layer; in addition, since step (S3) is an in-situ polymerization to form phenolic aldehyde, the stability of the structure is further promoted. The composite particles of phenolic aldehyde coated soft carbon are then carbonized and activated to form a composite porous carbon with a three-layer stable structure and a hard carbon coated soft carbon with a strong bond between the core and the shell. The inner layer of the three-layer structure is soft carbon, the middle layer is organosilicon-carbon, and the outer layer is hard carbon; finally, chemical vapor silicon deposition and carbon coating are performed to form a composite porous carbon-based negative electrode material of hard carbon coated soft carbon.
[0017] The degree of polymerization of the polyethylene glycol segment in the dopamine polyethylene glycol silane needs to be within the above range. If the degree of polymerization is too large, the active phenolic hydroxyl groups in the formed silicone-polydopamine will be relatively small, so that its binding force with the outer phenolic resin will be weaker, and the structural stability of the composite porous carbon will be poor, and the structure of some pores will collapse during activation. If the degree of polymerization is too small, the segment is too short, and it cannot effectively complement the dopamine monomer to form a dense middle layer, and the structural stability of the composite porous carbon will be poor, and the structure of some pores will collapse during activation.
[0018] Furthermore, in step (S1), the soft carbon material precursor is at least one of needle coke, petroleum coke, carbon fiber, and mesophase pitch microspheres.
[0019] Furthermore, in step (S1), the carbonization conditions are: keeping warm at 300-800°C for 3-8h under an inert atmosphere, the inert atmosphere is nitrogen and / or argon; the activation conditions are: using at least one of KOH, NaOH, KHCO3, and NaHCO3 as an activator, the mass ratio of the carbonized soft carbon material precursor to the activator is 1:2-5, the temperature is 700-900°C, and the time is 2-6h.
[0020] Furthermore, in step (S1), the particle size D50 of the soft carbon core particles is 3-10 μm, and the specific surface area is 1500-2500 m 2 / g, pore volume is 0.5~1.5 cm 3 / g.
[0021] Furthermore, in step (S2), the ratio of the soft carbon core particles to the oxidizing inorganic strong acid is 100g: (500~1000)mL; the oxidizing inorganic strong acid is 3~5mol / L nitric acid and / or sulfuric acid; the soaking conditions are: temperature 40~60°C, time 2~6h; the rinsing is rinsing with water until neutral; the drying is drying until the moisture content is <5wt%.
[0022] Furthermore, in step (S2), the amount ratio of the oxidized soft carbon, dopamine polyethylene glycol silane and aromatic hydrocarbon solvent is 100g: (60~90)mL: (500~1000)mL; the aromatic hydrocarbon solvent is at least one of toluene and xylene; and the conditions of the grafting reaction are: heating to 100~120°C and reflux reaction for 20~30h.
[0023] Furthermore, in step (S2), the amount of dopamine used is 8-15wt% of the modified soft carbon; the amount ratio of dopamine to Tris-HCl buffer solution is (5-10) g: 1000 mL, the concentration of the Tris-HCl buffer solution is 10-25 mM, and the pH is 8.0-9.0; the conditions for the in-situ copolymerization reaction are: stirring the reaction at 20-30°C for 4-8h; the drying conditions are: drying in a vacuum oven at 60-80°C for 12-24h.
[0024] Furthermore, in step (S3), the mass ratio of the composite particles of the organosilicon-polydopamine coated soft carbon to the phenolic monomer is 100:(25-40), preferably 100:(30-35).
[0025] Furthermore, in step (S3), the amount of the surfactant is 2-4wt% of the composite particles of silicone-polydopamine coated soft carbon; the molar ratio of the phenolic monomer to paraformaldehyde is 1:(1.5-1.6), and the molar amount of paraformaldehyde is calculated based on monomer formaldehyde; and the amount of the base catalyst is 2-3wt% of the phenolic monomer.
[0026] Furthermore, in step (S3), the surfactant is at least one of sodium succinate sulfonate, sodium dodecyl sulfonate, and sodium polyoxyethylene fatty alcohol ether sulfate; the concentration of alcohol in the alcohol aqueous solution is 15-30wt%, and the alcohol is ethanol, propanol or isopropanol; the phenolic monomer is at least one of phenol, cresol, and xylenol; and the base catalyst is ammonia water or an inorganic base, for example, the inorganic base is KOH or NaOH.
[0027] Furthermore, in step (S3), the conditions for the in-situ polymerization reaction are: temperature of 70-90°C, time of 3-6 hours; the conditions for the drying and curing are: temperature of 80-100°C, time of 24-48 hours.
[0028] Furthermore, in step (S4), the carbonization conditions are: keeping warm at 300-800°C for 3-8h under an inert atmosphere, the inert atmosphere is nitrogen and / or argon; the activation conditions are: using at least one of water vapor, carbon dioxide, ammonia, and hydrogen sulfide as an activator, the temperature is 800-1000°C, the time is 4-8h, and the ratio of the carbonized phenolic-coated soft carbon composite particles to the activator is 1g: (10-20)L.
[0029] Furthermore, in step (S4), the particle size D50 of the composite porous carbon of hard carbon coated with soft carbon is 5-15 μm, and the specific surface area is 1800-3000 m 2 / g, pore volume is 0.7~1.2cm 3 / g.
[0030] In step (S5), the process of vapor deposition of silicon and carbon coating is well known to those skilled in the art. If an organosilicon source gas is used for vapor deposition of silicon, the ratio of the composite porous carbon to the organosilicon source gas is 1 kg: (150-300) L, and the organosilicon source gas is selected from at least one of silane, disilane, trichlorosilane, silicon tetrachloride, and silicon tetrafluoride; if a gaseous carbon source is used for carbon coating, the ratio of the composite porous carbon to the gaseous carbon source is 1 kg: (250-500) L, and the gaseous carbon source is selected from at least one of C1-4 alkanes, C2-4 alkenes, and C2-4 alkynes.
[0031] In a second aspect, the present invention provides a composite porous carbon-based negative electrode material of hard carbon coated with soft carbon, which is prepared by the aforementioned preparation method.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1) The present invention uses dopamine polyethylene glycol silane to perform surface grafting modification on the porous soft carbon core to form modified porous carbon, and then in situ copolymerizes with dopamine monomer to form composite particles of organosilicon-polydopamine coated soft carbon; then in situ polymerizes the surface of the composite particles of organosilicon-polydopamine coated soft carbon to form phenolic resin, that is, a three-layer structure is formed, wherein the inner layer is soft carbon, the middle layer is organosilicon-polydopamine, and the outer layer is phenolic. Since it is an in-situ copolymerization, and the dopamine polyethylene glycol silane of a certain chain length can form an effective complement with the short-chain dopamine monomer, the organosilicon-polydopamine in the middle layer can densely, evenly and stably cover the soft carbon; at the same time, since the polydopamine in the middle layer has strong adhesion properties, and the abundant hydroxyl groups and amino groups in the polydopamine can form strong hydrogen bonding forces with the phenolic resin, thereby enhancing the bonding force between the two, so that the outer layer of the phenolic resin is firmly and stably coated on the middle layer; in addition, since step (S3) is an in-situ polymerization to form phenolic, the structural stability is further promoted. The composite particles of phenolic coated soft carbon are then carbonized and activated to form a composite porous carbon with a three-layer stable structure and a hard carbon-coated soft carbon with a strong bond between the core and the shell. The inner layer of the three-layer structure is soft carbon, the middle layer is organosilicon-carbon, and the outer layer is hard carbon; finally, chemical vapor silicon deposition and carbon coating are performed to form a composite porous carbon-based negative electrode material of hard carbon-coated soft carbon.
[0034] 2) The organosilicon-polydopamine in the middle layer of the composite porous carbon prepared by the present invention contains silicon and nitrogen elements, thereby forming a layer of organosilicon mesh film in the structure, and the Si-O bond has high bond energy and good stability; at the same time, nitrogen atom doping of the negative electrode material is achieved, which is beneficial to improving its electrochemical performance and extending the cycle life.
[0035] 3) The composite porous carbon-based negative electrode material of hard carbon coated with soft carbon prepared by the present invention has good cycle stability and excellent compressive resistance when used as a silicon-carbon negative electrode of a lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 TEM image of the composite porous carbon of hard carbon coated with soft carbon obtained in step (S4) of Example 1;
[0037] Figure 2 The first cycle charge and discharge curve of a lithium battery assembled with the composite porous carbon-based negative electrode material of hard carbon coated with soft carbon prepared in Example 1 at a rate of 0.1C. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0039] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0040] Dopamine polyethylene glycol triethoxysilane are all selected from Xi'an Kaixin Biotechnology Co., Ltd., among which,
[0041] Dopamine polyethylene glycol triethoxysilane X1, the number average molecular weight of the polyglycol segment is 500, that is, the average degree of polymerization n is about 11;
[0042] Dopamine polyethylene glycol triethoxysilane X2, the number average molecular weight of the polyglycol segment is 200, that is, the average degree of polymerization n is about 5;
[0043] Dopamine polyethylene glycol triethoxysilane X3, the number average molecular weight of the polyglycol segment is 650, that is, the average degree of polymerization n is about 15;
[0044] Dopamine polyethylene glycol triethoxysilane X4, the number average molecular weight of the polyglycol segment is 1000, that is, the average degree of polymerization n is about 23;
[0045] Dopamine polyethylene glycol triethoxysilane X5, the number average molecular weight of the polyglycol chain segment is 100; that is, the average polymerization degree n is about 2.
[0046] Example 1
[0047] (S1) The mesophase pitch microspheres were carbonized at 700°C for 4 h in a nitrogen atmosphere to obtain mesophase carbon microspheres; then the mesophase carbon microspheres were mixed with KOH in a mass ratio of 1:2.5 and activated at 800°C for 3 h in a nitrogen atmosphere; after the activation, the obtained material was added to a 1M hydrochloric acid solution at 40°C and stirred and washed until neutral, then washed with water, dried at 90°C for 12 h, and crushed to obtain soft carbon core particles with a D50 of 6.2 μm;
[0048] (S2) 300g of soft carbon core particles were placed in 2000mL of 3mol / L nitric acid, soaked at 50℃ for 3h, rinsed with pure water until neutral, and dried at 90℃ for 12h to obtain oxidized soft carbon; then 200g of oxidized soft carbon was dispersed in a mixture of 120mL of dopamine polyethylene glycol triethoxysilane X1 and 1500mL of toluene, refluxed at 100℃ for 24h under stirring, centrifuged after the reaction, and dried at 80℃ for 24h to obtain modified soft porous carbon; then 100g of modified soft carbon and 8g of dopamine were added to 1000mL of Tris-HCl buffer solution (concentration 20 mM, pH 8.5), stirred at 25℃ for 5h, and centrifuged, washed, and dried at 80℃ for 24h to obtain composite particles of organosilicon-polydopamine coated soft carbon after the reaction;
[0049] (S3) 100 g of organic silicon-polydopamine coated soft carbon composite particles and 3 g of sodium dodecyl sulfate are added to an ethanol-water mixture with an alcohol concentration of 20 wt% to form a suspension, and then 25 g of phenol, 12 g of paraformaldehyde, and 0.5 g of NaOH are added to the suspension, and the mixture is heated to 80° C. and stirred for reaction for 5 h; after the reaction is completed, the mixture is centrifuged and dried at 80° C. for curing for 24 h to obtain phenolic-coated soft carbon composite particles;
[0050] (S4) Take 50g of phenolic-coated soft carbon composite particles and carbonize them at 700°C in a nitrogen atmosphere for 5h; continue to heat up to 950°C, switch nitrogen to carbon dioxide, activate at a flow rate of 1.5L / min for 6h, switch carbon dioxide to nitrogen after activation, stop heating and naturally cool to room temperature to obtain a composite porous carbon of hard carbon-coated soft carbon;
[0051] (S5) 30 g of hard carbon-coated soft carbon composite porous carbon is placed in a CVD furnace with a rotation speed of 20 rpm. Helium is introduced at a flow rate of 5 L / min. After the temperature is raised to 600°C in a helium environment, the helium flow rate is maintained and monosilane gas is introduced at a flow rate of 0.1 L / min for chemical vapor deposition for 1 hour, so that the formed silicon particles are partially or completely attached to the pores of the porous carbon; after the silane deposition is completed, the monosilane gas is stopped, and helium is continuously introduced at a flow rate of 5 L / min to remove excess monosilane gas, and then acetylene gas is introduced at a flow rate of 0.2 L / min and maintained at 600°C for vapor deposition for 1 hour. The carbon particles formed after the decomposition of the acetylene gas are deposited on the surface of multiple carbon pieces, that is, a carbon coating layer is formed, and finally a composite porous carbon-based negative electrode material of hard carbon-coated soft carbon is obtained.
[0052] The specific surface area of the core particles obtained in step (S1) was 1815 m 2 / g, average pore volume 0.852cm 3 / g. The D50 of the composite porous carbon of hard carbon coated with soft carbon obtained in step (S4) was measured by a particle size analyzer to be 8.9 μm.
[0053] The TEM image of the composite porous carbon of hard carbon coated with soft carbon obtained in step (S4) is as follows: Figure 1 shown.
[0054] Example 2
[0055] The rest is the same as Example 1, except that in step (S2), the amount of dopamine polyethylene glycol triethoxysilane used is 150 mL, and the amount of dopamine used is 12 g.
[0056] Example 3
[0057] The rest is the same as Example 1, except that in step (S2), the amount of dopamine polyethylene glycol triethoxysilane used is 180 mL, and the amount of dopamine used is 15 g.
[0058] Example 4
[0059] The rest is the same as Example 1, except that in step (S2), dopamine polyethylene glycol triethoxysilane X2 is used instead of dopamine polyethylene glycol triethoxysilane X1.
[0060] Example 5
[0061] The rest is the same as Example 1, except that in step (S2), dopamine polyethylene glycol triethoxysilane X3 is used instead of dopamine polyethylene glycol triethoxysilane X1.
[0062] Example 6
[0063] The rest is the same as Example 1, except that in step (S3), the amount of phenol used is 30 g, the amount of paraformaldehyde used is 15 g, and the amount of NaOH used is 0.6 g.
[0064] Example 7
[0065] The rest is the same as Example 1, except that in step (S3), the amount of phenol used is 35 g, the amount of paraformaldehyde used is 17 g, and the amount of NaOH used is 0.7 g.
[0066] Example 8
[0067] The rest is the same as Example 1, except that in step (S3), the amount of phenol used is 40 g, the amount of paraformaldehyde used is 20 g, and the amount of NaOH used is 0.8 g.
[0068] Comparative Example 1
[0069] The rest is the same as Example 1, except that step (S2) is omitted, and the soft carbon core particles prepared in step (S1) are used in step (S3) to replace the porous carbon of the organosilicon-polydopamine coated soft carbon.
[0070] Comparative Example 2
[0071] The rest is the same as Example 1, except that in step (S2), dopamine polyethylene glycol triethoxysilane X4 is used instead of dopamine polyethylene glycol triethoxysilane X1.
[0072] Comparative Example 3
[0073] The rest is the same as Example 1, except that, in step (S2), dopamine polyethylene glycol triethoxysilane X5 is used instead of dopamine polyethylene glycol triethoxysilane X1.
[0074] Application Example 1
[0075] The composite porous carbon-based negative electrode material of hard carbon coated with soft carbon prepared in Example 1 was applied to the negative electrode of a lithium ion battery, assembled into a lithium battery, and its electrochemical performance was tested. Specific method: The composite porous carbon-based negative electrode material of hard carbon coated with soft carbon, Super P, carbon nanotubes, carboxymethyl cellulose and styrene-butadiene rubber composite binder were mixed in a mass ratio of 80:9.8:0.2:10 to form a slurry (the mass ratio of CMC and SBR was 1:1), and the slurry was applied to a copper foil with a 200 μm thick scraper, dried in a drying room, and placed in a vacuum dryer for 12 h to prepare a silicon-based negative electrode plate; then, metallic lithium was used as a counter electrode, polyolefin was used as a diaphragm, 1 mol / L LiPF6 (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1) was used as an electrolyte, 2% VC and 5% FEC were added to the electrolyte, and button batteries were assembled in an argon atmosphere in a Braun inert gas glove box in Germany. The battery assembled above was charged and discharged on a LAND charge and discharge tester, with a charge and discharge range of 50 mV to 1.5 V and a compaction density of 1.1 g / cm 3 After three charge and discharge cycles at a current density of 0.1 C (1 C = 1500 mA / g), rate charge and discharge tests were carried out at current densities of 1C and 5C, respectively.
[0076] Application Example 2-8
[0077] Other conditions are the same as those in Application Example 1, except that the composite porous carbon-based negative electrode materials of hard carbon coated with soft carbon are prepared according to Examples 2-8 respectively.
[0078] Comparative Application Examples 1-3
[0079] Other conditions are the same as those in Application Example 1, except that the composite porous carbon-based negative electrode materials of hard carbon coated with soft carbon are prepared according to Comparative Examples 1-3 respectively.
[0080] Testing and analysis
[0081] 1) The following performance tests were conducted on the composite porous carbon of hard carbon coated with soft carbon, and the data are shown in Table 1.
[0082] Specific surface area and pore size distribution determination: According to the gas adsorption BET method of GB / T 19587-2017, a low-temperature nitrogen adsorption experiment was carried out on the composite porous carbon of hard carbon coated with soft carbon prepared in the examples and comparative examples using a Tristar II 3020 fully automatic specific area and pore size analyzer produced by Micromeritics Instrument Corporation of the United States to determine its pore size distribution and specific surface area.
[0083] Table 1 Performance test of composite porous carbon coated with hard carbon and soft carbon
[0084] .
[0085] It can be seen from Table 1 that the composite porous carbon of hard carbon coated with soft carbon prepared in the preparation example of the present invention has a higher specific surface area than the specific surface area of the soft carbon core particles; at the same time, the middle layer of silicone-polydopamine contains silicon and nitrogen elements, which realizes the formation of a layer of silicone mesh film and nitrogen atom doping in the structure, which is beneficial to the improvement of electrochemical performance.
[0086] The specific surface area of the composite porous carbon of hard carbon coated with soft carbon obtained in Comparative Example 1 is lower than that in the embodiment. The possible reason is that the composite particles of phenolic coated soft carbon formed after omitting step (S2) do not contain silicone-polydopamine intermediate layer, and the bonding force between the soft carbon inner core layer and the hard carbon outer layer after carbonization is not strong, and the structure of some pores will collapse in the subsequent activation and pore-forming process; and because there is no silicone-polydopamine intermediate layer, the composite porous carbon obtained in Comparative Example 1 also does not contain nitrogen element.
[0087] The specific surface area of the composite porous carbon of hard carbon coated with soft carbon obtained in Comparative Example 2 is lower than that in the embodiment. The possible reason is that the degree of polymerization of dopamine polyethylene glycol triethoxysilane is relatively large, and the active phenolic hydroxyl groups in the formed silicone-polydopamine are relatively small, so its bonding force with the outer layer of phenolic resin will be weaker, and the structural stability of the composite porous carbon will be poor, and the structure of some pores will collapse during activation.
[0088] The specific surface area of the composite porous carbon of hard carbon coated with soft carbon obtained in Comparative Example 3 is lower than that of the embodiment. The possible reason is that the degree of polymerization of dopamine polyethylene glycol triethoxysilane is relatively small, and the chain segment is too short, which cannot effectively complement the dopamine monomer to form a dense intermediate layer. As a result, the structural stability of the composite porous carbon is poor, and the structure of some pores will collapse during activation.
[0089] Compared with the surface area of the soft carbon core particles, it can be seen that the specific surface area of the composite porous carbon prepared in Examples 1, 2, and 3 has decreased. This is also due to the instability of its structure and the collapse of the pore structure during the subsequent carbonization and activation process.
[0090] 2) Electrochemical performance test: The batteries assembled in the application examples and comparative application examples were charged and discharged on a LAND charge and discharge tester, with a voltage range of 50 mV to 1.5 V and a compaction density of 1.1 g / cm3. Three charge and discharge tests were performed at a current density of 0.1 C (1 C = 1500 mA / g). The battery performance test data is shown in Table 2.
[0091] Table 2 Electrochemical performance test
[0092] .
[0093] From the data in Table 2, it can be seen that when the composite porous carbon-based negative electrode material of hard carbon coated with soft carbon prepared by the preparation method of the present invention is used as the negative electrode of a lithium battery, its first reversible capacity reaches more than 1850mAh / g, the first coulomb efficiency reaches more than 88%, and the discharge capacity retention rate after 100 cycles can reach more than 89%, indicating that the assembled lithium battery has good cycle stability and charge and discharge capacity. And the first efficiency attenuation rate of the composite porous carbon-based negative electrode material of hard carbon coated with soft carbon prepared by the method of the present invention is less than 5% under a pressure of 10t, indicating that it has good structural stability.
[0094] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite porous carbon-based negative electrode material of hard carbon coated with soft carbon, characterized in that: The following steps are involved: (S1) carbonizing, activating and crushing a soft carbon material precursor to obtain soft carbon core particles; (S2) soaking the soft carbon core particles in an oxidizing inorganic strong acid, rinsing and drying after soaking to obtain oxidized soft carbon; then dispersing the oxidized soft carbon in a mixed solution of dopamine polyethylene glycol silane and an aromatic solvent for grafting reaction to obtain modified soft carbon; then adding the modified soft carbon and dopamine to a Tris-HCl buffer solution for in-situ copolymerization reaction, and after the reaction is completed, centrifuging, washing, and drying to obtain composite particles of organosilicon-polydopamine coated soft carbon; the structural formula of the dopamine polyethylene glycol silane is: ; Wherein, R is methyl or ethyl, and n is an integer of 5 to 15; (S3) adding the composite particles of organosilicon-polydopamine coated soft carbon and a surfactant into an alcohol aqueous solution to form a suspension, then adding a phenolic monomer, polyformaldehyde and an alkali catalyst to the suspension, heating the suspension to perform an in-situ polymerization reaction; after the reaction is completed, centrifuging, drying and solidifying the suspension to obtain composite particles of phenolic coated soft carbon; (S4) The composite particles of phenolic coated soft carbon are carbonized and activated to obtain composite porous carbon of hard carbon coated soft carbon; (S5) Chemical vapor deposition is performed on the composite porous carbon using an organic silicon source gas, so that part or all of the nano-silicon particles are attached to the pores of the porous carbon; then, a gas-phase carbon source is used to perform vapor deposition to form a carbon coating layer, thereby obtaining a composite porous carbon-based negative electrode material in which hard carbon is coated with soft carbon.
2. The preparation method according to claim 1, characterized in that: In step (S1), the soft carbon material precursor is at least one of needle coke, petroleum coke, carbon fiber, and mesophase pitch microspheres; and / or The carbonization conditions are: 300-800°C for 3-8h under an inert atmosphere, wherein the inert atmosphere is nitrogen and / or argon; the activation conditions are: using at least one of KOH, NaOH, KHCO3, and NaHCO3 as an activator, the mass ratio of the carbonized soft carbon material precursor to the activator is 1:2-5, the temperature is 700-900°C, and the time is 2-6h; and / or The particle size D50 of the soft carbon core particles is 3-10 μm, and the specific surface area is 1500-2500 m 2 / g.
3. The preparation method according to claim 1, characterized in that: In step (S2), the ratio of the soft carbon core particles to the oxidizing inorganic strong acid is 100g: (500~1000)mL; the oxidizing inorganic strong acid is 3~5mol / L nitric acid and / or sulfuric acid; the soaking conditions are: temperature 40~60°C, time 2~6h; the rinsing is rinsing with water until neutral; the drying is drying until the moisture content is <5wt%.
4. The preparation method according to claim 1, characterized in that: In step (S2), the amount ratio of the oxidized soft carbon, dopamine polyethylene glycol silane and aromatic hydrocarbon solvent is 100g: (60-90)mL: (500-1000)mL; the aromatic hydrocarbon solvent is at least one of toluene and xylene; the grafting reaction conditions are: heating to 100-120°C and reflux reaction for 20-30h.
5. The preparation method according to claim 1, characterized in that: In step (S2), the amount of dopamine used is 8-15wt% of the modified soft carbon; the ratio of dopamine to Tris-HCl buffer solution is (5-10) g:1000 mL, the concentration of Tris-HCl buffer solution is 10-25 mM, and the pH is 8.0-9.0; the conditions for the in-situ copolymerization reaction are: stirring the reaction at 20-30°C for 4-8h; the drying conditions are: drying in a vacuum oven at 60-80°C for 12-24h.
6. The preparation method according to claim 1, characterized in that: In step (S3), the mass ratio of the composite particles of the organosilicon-polydopamine coated soft carbon to the phenolic monomer is 100:(25-40).
7. The preparation method according to claim 6, characterized in that: In step (S3), the mass ratio of the composite particles of the organosilicon-polydopamine coated soft carbon to the phenolic monomer is 100:(30-35).
8. The preparation method according to claim 1, characterized in that: In step (S3), the amount of the surfactant is 2-4wt% of the composite particles of organosilicon-polydopamine coated soft carbon; the molar ratio of the phenolic monomer to the paraformaldehyde is 1:(1.5-1.6), and the molar amount of the paraformaldehyde is calculated as monomer formaldehyde; the amount of the base catalyst is 2-3wt% of the phenolic monomer; and / or The surfactant is at least one of sodium succinate sulfonate, sodium dodecyl sulfonate, and sodium polyoxyethylene fatty alcohol ether sulfate; the concentration of alcohol in the alcohol aqueous solution is 15-30wt%, and the alcohol is ethanol, propanol, or isopropanol; the phenolic monomer is at least one of phenol, cresol, and xylenol; the base catalyst is ammonia water or an inorganic base; and / or The conditions for the in-situ polymerization reaction are: temperature of 70-90° C., time of 3-6 hours; the conditions for the drying and curing are: temperature of 80-100° C., time of 24-48 hours.
9. The preparation method according to claim 1, characterized in that: In step (S4), the carbonization conditions are: keeping warm at 300-800°C for 3-8h under an inert atmosphere, the inert atmosphere is nitrogen and / or argon; the activation conditions are: using at least one of water vapor, carbon dioxide, ammonia, and hydrogen sulfide as an activator, the temperature is 800-1000°C, the time is 4-8h, and the ratio of the carbonized phenolic-coated soft carbon composite particles to the activator is 1g: (10-20)L.
10. The preparation method according to claim 1, characterized in that: In step (S4), the particle size D50 of the composite porous carbon of hard carbon coated with soft carbon is 5-15 μm, and the specific surface area is 1800-3000 m 2 / g, pore volume is 0.7~1.2cm 3 / g.
Citation Information
Patent Citations
A soft and hard carbon composite porous anode material for sodium-ion batteries and its preparation method
CN111293301B
A method for preparing a hard carbon-coated soft carbon composite material
CN113889593B
Preparation method of hard carbon coated soft carbon composite material
CN113889593A
Silicon-carbon negative electrode and preparation method and application thereof
CN116314630A